2015
DOI: 10.3141/2516-07
|View full text |Cite
|
Sign up to set email alerts
|

Before-and-After Empirical Bayes Evaluation of Automated Mobile Speed Enforcement on Urban Arterial Roads

Abstract: Speeding is a leading factor in road collisions and is found to contribute to approximately one-third of all fatal collisions. Speed enforcement is one of the most common countermeasures used to reduce speed. However, a gap exists in the literature regarding the effectiveness of automated mobile photo enforcement on urban arterial roads. This study addresses this gap using the before-and-after empirical Bayes method to account for regression to the mean effects and other confounding factors. Locally developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…The study adopted a conventional analysis approach, which has been known to lead to biased conclusions owing to the method’s inability to account for RTM effects and other confounding factors. The before-and-after EB approach used in this study can address all of the major limitations that are associated with the use of conventional safety analysis techniques ( 29 , 30 ). In addition, the monetary value of the expected change in frequency of collisions is estimated, which may help in assessing the economic feasibility of anti-icing WRM and provide WRM agencies with useful information about the economic performance of achieving BP using anti-icing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study adopted a conventional analysis approach, which has been known to lead to biased conclusions owing to the method’s inability to account for RTM effects and other confounding factors. The before-and-after EB approach used in this study can address all of the major limitations that are associated with the use of conventional safety analysis techniques ( 29 , 30 ). In addition, the monetary value of the expected change in frequency of collisions is estimated, which may help in assessing the economic feasibility of anti-icing WRM and provide WRM agencies with useful information about the economic performance of achieving BP using anti-icing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was also found that there was a time-halo effect of at least two days after the police vehicles had left. Furthermore, several studies found speed enforcement to be not only effective but also offer considerable safety improvements (Gouda & El-Basyouny 2017;Li et al 2015;Elliott & Broughton 2005;Wrapson et al 2006;Walter & Broughton 2011;Cruzado & Donnel 2009). In a review that was conducted by Elliott & Broughton (2005), it was shown that a reduction of 4.8 km/h in the mean speed was achieved by using stationary and visible enforcement.…”
Section: Previous Studiesmentioning
confidence: 99%
“…This could be achieved through improving the design and safety of road facilities as well as launching integrated initiatives that aim to modifying drivers' behavior and prevent collisions (Shalkamy et al 2018;Shalkamy & El-Basyouny 2020) Many factors contribute to road collisions such as limited sight distance, inclement weather, driver fatigue, and, most importantly, speeding-which was estimated to be the main contributing factor for 30% of fatal collisions (Shalkamy et al 2020;Richards et al 1985). It is generally accepted that speeding is a causal factor in collision occurrence with significant implications to the likely outcome of a road collision (Li et al 2015). Speed could be related to safety in two different ways.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations